Investigation of aluminum cooling coil in condenser application using computational fluid dynamic (CFD) - Mohd Hairul Nizam, Mohamed (2008)
Heat exchanger or condenser has been used extensively in the world to transfer heat from one liquid to other liquid are widely used in air-conditioning, boiler, chiller and so on. The thesis present the improvement and development of heat transfer that occur in the condenser by changing the coil inside the condenser to predict the thermal performance in the condenser. Aluminum is chosen as our material because of the fact that aluminum has good machinability also it is easy to design and machine. In fact the marketable of aluminum are more impressive compared to copper where aluminum is cheaper and easy to find. This aluminum material coil will increase the efficiency of the condenser due to a few factors. The specific heat at constant pressure (ce ) is the main factor that will increase the efficiency of the condenser. The condenser real-time model is done by using SolidWork design software. A method of determining thermal performance of a condenser is chosen by simulating the condenser using Computational Fluid Dynamic (CFD) to obtain the result. The result we gain from COSMOSF1oWorks then will be compare among those two materials. By replacing the copper coil to aluminum coil we expected and achieve further improvement that aluminum coil are better material to transfer heat rather than aluminum coil.